Juan Rodolfo Wilcock, a case of linguistic self-exile in two stages - Martínez Pérsico, Marisa (Oltreoceano - Rivista sulle migrazioni, 2024)
This paper focuses on the case study of J.R. Wilcock, a multilingual Italian-Argentine writer who changed the language of literary expression, going from the native language (River Plate Spanish) to the acquired language (Italian). Wilcock’s is an example of voluntary territorial and linguistic exile, brought about by his differences with Peronism and by the desire to return to his Italian (biological family) and Latin (linguistic family) roots. This transition from one language to the other, a way of territorial and symbolic uprooting at the same time, was progressive. We identify two phases: the consecutive self-translation from Spanish to Italian practiced in Poesie spagnole, a book published in 1963 with a poetic selection from the 40s and 50s, and the adoption of the second language from Luoghi comuni (1961). Then, he will no longer write in Spanish or self-translate from L2 to L1. Hypotheses are presented about the reasons for code switching linked to the principle of linguistic complementarity, the rejection of transcreation and distrust in the functional adherence of any translation. Wilcock’s decision to translate himself was a way of exercising control over the fidelity of the Spanish originals that he wanted to present to the Italian public without losing the opportunity to disseminate a representative sample of his Argentine poetic prehistory and to pay tribute to him, still with nostalgia. Later, his voluntary exile would be fulfilled in the language, with the definitive change to Italian of his ancestors on the maternal side. In these compositions he will renounce vernacular, popular and regional brands (both Italian and Spanish) in a diachronic travel back to the common ideal of a lost Latinity. Wilcock’s linguistic exile questions the idea of “border” understood as a defining space of a subject’s identity, revealing the capacity of language to construct new personal and literary identities throughout life.